Investigation of the 18-Year Status and Changes of Mixed Stands in Europe - AKTÜRK, Emre; ALTUNEL, Arif Oguz; KARA, Ferhat (Bartin Orman Fakultesi Dergisi, 2020)
Forests play essential roles for the protection of the earth when we are struggling with global climate change. It is necessary to examine the current status of the forests and their changes over time in order to determine the precautions to be taken in the future to overcome the environmental issues associated with the climate change. For this reason, the current status and the 18-year change of European Continent mixed forest stands in acreage were examined in this article. The Coordination of Information on the Environment (CORINE) land cover datasets belonging to 2000, 2006, 2012 and 2018 were used for the analyses in the study. Approximately 2.8 million hectares of mixed forestland have been lost in the last eighteen years in Europe, which has approximately 31 million hectares of mixed forest stands as of 2018. It was determined that this decrease was mostly caused by the change during the period of 2006-2012. In addition, it was revealed that mixed forests of Finland, Germany and Turkey dramatically suffered a high rate of destruction in the last eighteen years as a result of this study.
Keywords: 13. Climate action; 15. Life on land